2016
DOI: 10.1016/j.jvs.2015.10.100
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of revision using distal inflow and distal revascularization-interval ligation for the management of severe access-related hand ischemia

Abstract: In this preliminary study, the RUDI demonstrated similar patency, symptom resolution, and survival compared with the DRIL for patients with severe ARHI. All-cause mortality after any procedure for severe steal syndrome is high, and the particular intervention for management of steal must account for anatomic-, patient-, and disease-related considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Different surgical and endovascular techniques to resolve HAIDI symptoms have been described. 1,2931 However, in our series one patient suffered from severe symptoms and therefore surgical access ligation was necessary for upper limb salvage. The decision for access abandonment and against other possible surgical procedures as distal reconstruction, interval ligation, or inflow improvement was based on the severity of symptoms in this multimorbid female patient.…”
Section: Discussionmentioning
confidence: 71%
“…Different surgical and endovascular techniques to resolve HAIDI symptoms have been described. 1,2931 However, in our series one patient suffered from severe symptoms and therefore surgical access ligation was necessary for upper limb salvage. The decision for access abandonment and against other possible surgical procedures as distal reconstruction, interval ligation, or inflow improvement was based on the severity of symptoms in this multimorbid female patient.…”
Section: Discussionmentioning
confidence: 71%
“…For instance, one study demonstrated 78% 3 year patency rates in patients with hand ischaemia. 30 A second study found 87% 1 year secondary patency rates in 29 patients with hand ischaemia or HFA. 13 A third study using PTFE interposition grafts reported 77% secondary patency rates after 16 months.…”
Section: Discussionmentioning
confidence: 97%
“…[8][9][10] Three-and four-year survival rates were approximately 50% and 42% in two other samples having hand ischemia. 23,24 Survival rates of HD patients with or without HAIDI were never compared in a single dialysis facility. The present single center study hypothesized that patients with severe HAIDI (Grade IIb-IV) had lower survival compared with HD patients with mild (Grade I-IIa), or no HAIDI.…”
Section: Discussionmentioning
confidence: 99%